KECERDASAN EMOSIONAL PESERTA DIDIK SEKOLAH DASAR - Awang, Imanuel Sairo; Merpirah, Metah; Mulyadi, Yohanes Berkhmas (Profesi Pendidikan Dasar, 2019)
This study aimed to describe emotional intelligence of Grade IV Students of elementary school. This study used descriptive method with a qualitative approach. The data collection using emotional intelligence questionnaires and interview. Based on the results the students’ emotional intelligence charactheristic was variated. The student ability to recognize and manage emotions was lacked. In addition, the ability to motivate oneself, recognize the emotions of others and the ability to develop relationships was good. Nevertheless there was tendency for the characteristics of good emotional intelligence to contribute to the learning achievements of students. This is indicated by 63.64% of students characterized by good emotional intelligence also supported by learning outcomes with 54.55% of students whose learning outcomes are complete.